A research framework for the development and implementation of interventions preventing work-related musculoskeletal disorders - Van Der Beek, A.; Dennerlein, J.; Huysmans, M.; Mathiassen, S.; Burdorf, A.; Van Mechelen, W.; Van Dieën, J.; Frings-Dresen, M.; Holtermann, A.; Janwantanakul, P.; Van Der Molen, H.; Rempel, D.; et al. (Tyoterveyslaitos, 2017)
Objectives: Work-related musculoskeletal disorders (MSD) are highly prevalent and put a large burden on (working) society. Primary prevention of work-related MSD focuses often on physical risk factors (such as manual lifting and awkward postures) but has not been too successful in reducing the MSD burden. This may partly be caused by insufficient knowledge of etiological mechanisms and/or a lack of adequately feasible interventions (theory failure and program failure, respectively), possibly due to limited integration of research disciplines. A research framework could link research disciplines thereby strengthening the development and implementation of preventive interventions. Our objective was to define and describe such a framework for multi-disciplinary research on work-related MSD prevention. Methods: We described a framework for MSD prevention research, partly based on frameworks from other research fields (ie, sports injury prevention and public health). Results: The framework is composed of a repeated sequence of six steps comprising the assessment of (i) incidence and severity of MSD, (ii) risk factors for MSD, and (iii) underlying mechanisms; and the (iv) development, (v) evaluation, and (vi) implementation of preventive intervention(s). Conclusions: In the present framework for optimal work-related MSD prevention, research disciplines ar e linked. This framework can thereby help to improve theories and strengthen the development and implementation of prevention strategies for work-related MSD.